Early Hospital Arrival After Acute Ischemic Stroke Is Associated With Family Members' Knowledge About Stroke - Wang, Rongyu; Wang, Zhiqiang; Yang, Dongdong; Wang, Jian; Gou, Chongji; Zhang, Yaodan; Xian, Liulin; Wang, Qingsong (Frontiers in Neurology, 2021)
Background and Purpose: Prehospital delay is the major factor limiting intravenous thrombolysis and mechanical thrombectomy in acute ischemic stroke (AIS). This study aimed to: (1) identify factors related to prehospital delay and (2) determine the impact of recognition and behavior of family members on patient delay. Methods: A cross-sectional, multicenter study was conducted at 6 teaching hospitals in China between December 1, 2018 and November 30, 2019. Patients who experienced AIS within 7 days of onset were interviewed. Results: Of 1,782 consecutive patients (male, 57.97%; mean age, 66.3±9.65 years) who had an AIS, 267 (14.98%) patients arrived within 4.5 hours and 722 (40.52%) patients arrived within 6 hours of stroke onset. Age over 65 years (OR, 2.009; 95% CI, 1.014-3.982), prior stroke (OR, 3.478; 95% CI, 1.311-9.229), blurred vision (OR, 3.95; 95% CI, 1.71-9.123), and patients deciding to seek medical help (OR, 3.097; 95% CI, 1.417-6.769) were independently associated with late arrival. In contrast, sudden onset of symptoms (OR, 0.075; 95% CI, 0.028-0.196), the National Institutes of Health Stroke Scale 7-15 (OR, 0.093; 95% CI, 0.035-0.251), consciousness disturbance (OR, 0.258; 95% CI, 0.091-0.734), weakness (OR, 0.265; 95% CI, 0.09-0.784), arrival by ambulance (OR, 0.102; 95% CI, 0.049-0.211), decision time <30 minutes (OR, 0.008; 95% CI, 0.003-0.018), and family member understanding stroke requires early treatment (OR, 0.224; 95% CI, 0.109-0.462) were independently associated with early arrival. Conclusions: The prehospital delay in China lags behind Western countries. Recognition and behavior of stroke patients’ family members may play a key role in early arrival.